Analysis of The Influence of Work Discipline And Employee Motivation on Employee Performance BMT Beringharjo - Rahma Yudi Astuti; Muhammad Wafiyuddin Balya Mahdi (University of Darussalam Gontor, 2023)
Human resources (HR) will play a positive or negative role in the performance of a company by applying work discipline and work motivation. However, BMT Beringharjo Still long work motivations based on Islamic values to improve HR performance. In addition, the success of the company is largely determined by the style of work motivation that exists in the organization that will affect employee performance. BMT Beringharjo is an Islamic-based which implements in accordance with the company's VISION, namely